Experimental study on the flexural behavior of ferrocement slab panels with supplementary cementitious silica fume and fiber materials - Pooja Kaushik; Owais Ul Hassan; Mohammed Sharif (Discover Civil Engineering)
Abstract Ferrocement is a composite construction material with slender sections or panels, a rich cementitious mortar, and steel wire mesh as its principal reinforcing agent. The mortar matrix is designed to achieve optimal strength, density, impermeability, and workability, minimizing void formation and preventing map cracking. A study evaluated the workability and flexural strength of mortars prepared using three types of fine aggregates: Badarpur sand, Yamuna River sand, and Kilned Brick Powder. The mortar classifications included conventional mortar compositions (MCS), mortars with flyash and Silica Fume (MFSS), and mortars with flyash, silica fume, and human hair (MFSHS). The results showed that mixes incorporating these materials significantly improved workability, with MFSS-2 (Portland cement, Yamuna sand, plus 10% FA and 6% SF) showing the highest increase (42.50%). The high-strength formulations with supplementary materials were superior in terms of stiffness and structural integrity, with MFSHS-1 (Portland cement, Badarpur sand, 10% FA, 6% SF, and 1% HH fiber) showing the least deflection for any given load. The addition of 1% human hair fibers in the mortar matrix improved flexural strength in panels, acting as micro-reinforcements, enhancing the tensile strength alongwith mortar ductility.